The comparative role of intervening and independent variables in the adoption behaviour of maize growers in Njombe district, Tanzania - Duvel, G.H. (Gustav Heinrich) (University of Pretoria, 2013)
Thesis (PhD(Agrarian Extension))--University of Pretoria, 2008.